SARS-CoV-2/ACE2 Interaction Suppresses IRAK-M Expression and Promotes Pro-Inflammatory Cytokine Production in Macrophages - Pantazi, Ioanna; Al-Qahtani, Ahmed A.; Alhamlan, Fatimah S; Alothaid, Hani; Matou-Nasri, Sabine; Sourvinos, George; Vergadi, Eleni; Tsatsanis, Christos (Frontiers in Immunology, 2021)
The major cause of death in SARS-CoV-2 infected patients is due to de-regulation of the innate immune system and development of cytokine storm. SARS-CoV-2 infects multiple cell types in the lung, including macrophages, by engagement of its spike (S) protein on angiotensin converting enzyme 2 (ACE2) receptor. ACE2 receptor initiates signals in macrophages that modulate their activation, including production of cytokines and chemokines. IL-1R-associated kinase (IRAK)-M is a central regulator of inflammatory responses regulating the magnitude of TLR responsiveness. Aim of the work was to investigate whether SARS-CoV-2 S protein-initiated signals modulate pro-inflammatory cytokine production in macrophages. For this purpose, we treated PMA-differentiated THP-1 human macrophages with SARS-CoV-2 S protein and measured the induction of inflammatory mediators including IL6, TNFα, IL8, CXCL5, and MIP1a. The results showed that SARS-CoV-2 S protein induced IL6, MIP1a and TNFα mRNA expression, while it had no effect on IL8 and CXCL5 mRNA levels. We further examined whether SARS-CoV-2 S protein altered the responsiveness of macrophages to TLR signals. Treatment of LPS-activated macrophages with SARS-CoV-2 S protein augmented IL6 and MIP1a mRNA, an effect that was evident at the protein level only for IL6. Similarly, treatment of PAM3csk4 stimulated macrophages with SARS-CoV-2 S protein resulted in increased mRNA of IL6, while TNFα and MIP1a were unaffected. The results were confirmed in primary human peripheral monocytic cells (PBMCs) and isolated CD14+ monocytes. Macrophage responsiveness to TLR ligands is regulated by IRAK-M, an inactive IRAK kinase isoform. Indeed, we found that SARS-CoV-2 S protein suppressed IRAK-M mRNA and protein expression both in THP1 macrophages and primary human PBMCs and CD14+ monocytes. Engagement of SARS-CoV-2 S protein with ACE2 results in internalization of ACE2 and suppression of its activity. Activation of ACE2 has been previously shown to induce anti-inflammatory responses in macrophages. Treatment of macrophages with the ACE2 activator DIZE suppressed the pro-inflammatory action of SARS-CoV-2. Our results demonstrated that SARS-CoV-2/ACE2 interaction rendered macrophages hyper-responsive to TLR signals, suppressed IRAK-M and promoted pro-inflammatory cytokine expression. Thus, activation of ACE2 may be a potential anti-inflammatory therapeutic strategy to eliminate the development of cytokine storm observed in COVID-19 patients.